2016
DOI: 10.1002/bjs.10258
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and substance abuse, depression and suicide attempts after Roux-en-Y gastric bypass surgery

Abstract: Patients who have undergone RYGB are at an increased risk of being diagnosed with alcohol and substance use, with an increased rate of attempted suicide compared with a non-obese general population cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
74
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 28 publications
(37 reference statements)
6
74
1
2
Order By: Relevance
“…Our finding of an increased use of hypnotics and/or sedatives after gastric bypass is consistent with that from an uncontrolled 2-year follow-up study of 165 Norwegian patients (22) and from a Swedish study comparing 3,139 gastric bypass patients with 31,390 general population controls over 4 years of follow-up (23). Note that the Swedish study did not match for baseline BMI.…”
Section: Discussionsupporting
confidence: 87%
“…Our finding of an increased use of hypnotics and/or sedatives after gastric bypass is consistent with that from an uncontrolled 2-year follow-up study of 165 Norwegian patients (22) and from a Swedish study comparing 3,139 gastric bypass patients with 31,390 general population controls over 4 years of follow-up (23). Note that the Swedish study did not match for baseline BMI.…”
Section: Discussionsupporting
confidence: 87%
“…2,5,6 However, findings from longitudinal studies of AUD-related outcomes prior to and following bariatric surgery are inconsistent 3-5 and few studies have long-term follow-up or evaluation of non-alcohol SUD, 3,4 such that we have little understanding of whether the risk of AUD or non-alcohol SUD changes over time and the proportion of post-surgical patients that are ultimately affected. Recent literature reviews of AUD or SUD and bariatric surgery concluded there is a need for large, prospective, longitudinal studies that extend beyond two years, separate alcohol from other drug use, use standardized assessments, account for type of bariatric surgical procedure and identify risk factors for development of post-surgery AUD.…”
Section: Introductionmentioning
confidence: 99%
“…5-7 Recent populationbased observational studies have identified an increased risk of suicide and self-harm among patients who underwent surgery, compared to non-surgically treated individuals and the general population.Moreover, longitudinal studies have demonstrated that the risk of self-harm increases following treatment in those patients who choose to undergo surgery. [8][9][10][11][12] Despite these reports, there is sparse evidence from randomized trials assessing the risk of suicidality and self-harm following bariatric Alejandro Szmulewicz, Kerollos N. Wanis and Ashley Gripper contributed equally to this work.…”
mentioning
confidence: 99%